Faktor-Faktor yang Mempengaruhi Kinerja Guru pada Masa Pandemi Covid-19 (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Improving teacher performance is very important for every school to facilitate the teaching and learning process in schools. The purpose of this study was to determine the effect of professional competence, work motivation and work discipline on teacher performance during the COVID-19 pandemic at SMP PGRI 8 Denpasar partially and simultaneously. This study used a population of 41 people and a sample that took the entire population, therefore the sampling method used was saturated sampling. Data analysis was performed using multiple linear regression analysis method. The results of this study indicate that professional competence, work motivation and work discipline can improve teacher performance during the COVID-19 pandemic positively and significantly. Suggestions in this study are to improve teacher performance by considering the factors of professional competence, work motivation and work discipline.